2012
DOI: 10.1111/j.1365-2133.2012.11037.x
|View full text |Cite
|
Sign up to set email alerts
|

A study on the epidemiology of rosacea in the U.K.

Abstract: We quantified incidence rates and characteristics of patients with rosacea diagnosed in clinical practice in a large epidemiological study using primary care data from the U.K. Smoking was associated with a substantially reduced risk of developing rosacea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
159
4
35

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(208 citation statements)
references
References 44 publications
(121 reference statements)
10
159
4
35
Order By: Relevance
“…These factors tend to be specific to each individual. A recent large epidemiologic study revealed that alcohol consumption is associated with only a small increase in risk of developing rosacea, whereas smoking may actually substantially reduce such risk (9) . Patients with ocular rosacea may complain of foreign body sensation, dryness, itching, photophobia and tearing (10,60) .…”
Section: Clinical Findings Rosaceamentioning
confidence: 99%
See 1 more Smart Citation
“…These factors tend to be specific to each individual. A recent large epidemiologic study revealed that alcohol consumption is associated with only a small increase in risk of developing rosacea, whereas smoking may actually substantially reduce such risk (9) . Patients with ocular rosacea may complain of foreign body sensation, dryness, itching, photophobia and tearing (10,60) .…”
Section: Clinical Findings Rosaceamentioning
confidence: 99%
“…Debris in the tear film may also be present. Recurrent hordeolum/chalazion and tear film insufficiency are commonly observed as a consequence of meibomian gland dysfunction (9,15) . Dry eyes, with abnormal Schirmer test, were reported in 56-62.5% of patients with ocular rosacea (24,51,63) .…”
Section: Eyelids and Tear Filmmentioning
confidence: 99%
“…Moreover, inflammatory changes in distant organs, such as eyes, arteries, and pancreas, have been described among active smokers (7)(8)(9). Conversely, active smoking has been linked to a decreased risk of ulcerative colitis, an inflammatory bowel disease (10), and rosacea, an inflammatory skin disorder (11). Thus, the direct inflammatory effects of cigarette smoking on several organs, including the prostate, remain to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Согласно данным, полученным за последнее де-сятилетие, заболеваемость розацеа в разных странах составляет от 1 до 22% населения [1][2][3][4][12][13][14][15].…”
Section: Discussionunclassified
“…Употребление алкоголя было связано с минималь-ным риском повышения заболеваемости. Табакоку-рение достоверно снижало вероятность заболевания розацеа [12].…”
Section: распространенность розацеа в разных странахunclassified